Diced Cartilage Rhinoplasty for Cleft Nose Deformities: Determining the Flexibility of the Cartilage Framework. Issue 2 (March 2021) - Lonic, Daniel; Hsiao, Yen-Chang; Huang, Jung-Ju; Chang, Chun-Shin; Chen, Jyh-Ping; Denadai, Rafael; Bosselmann, Talia; Kehrer, Andreas; Prantl, Lukas; Lo, Lun-Jou; Chen, Yu-Ray
Abstract : Background: The objective of this trial is to evaluate the flexibility of the cartilaginous component of the cleft nose after diced cartilage rhinoplasty by determining the degree of possible bending in relation to the vertical nasal dorsum axis and to compare with to a control group of the unaffected population. Patients and Methods: Fifteen cleft nose patients with diced cartilage rhinoplasty were included in this study, as well as a control group of 15 unaffected individuals. The angle of maximum nasal bending is measured between the basic and maximum bending axis and performed by the same rater twice at least 2 weeks apart to account for intrarater reliability. Study groups were compared with Fisher and independent t test. Results: The maximum bending to the left side was 16.10 ± 5.03 degrees for the study group and 23.95 ± 6.54 degrees for the control group ( P = 0.001). The maximum bending to the right side were 16.54 ± 6.73 degrees for the study group and 23.00 ± 8.88 degrees for the control group ( P = 0.034). Conclusion: Diced cartilage graft injection for dorsal augmentation yields reproducible and esthetically pleasing outcomes with good flexibility and natural feel of the nasal tip. Although there is a significant difference compared with a nonaffected control group in maximum bending capacity, all patients in this study were satisfied with the results.